Omnichannel Marketing in the Digital Age: Creating Consistent, Personalized and Connected Customer Experiences - Darvidou, Konstantia (Technium Business and Management, 2024)
This paper explores the transformative potential of omnichannel marketing as a strategic approach that integrates multiple online and offline channels to create a cohesive and seamless customer experience. As consumer expectations for convenience, personalization, and immediacy continue to rise, brands must move beyond traditional multichannel strategies to deliver interconnected experiences that resonate with the modern, digitally-savvy customer. The paper delves into the principles and significance of omnichannel marketing, emphasizing the importance of creating a unified brand presence across diverse touchpoints. Key elements such as the integration of Customer Data Platforms (CDPs), Customer Relationship Management (CRM) systems, and marketing automation tools are discussed for their role in enabling businesses to gather, analyze, and utilize customer data effectively. Moreover, the paper examines the various challenges associated with implementing an omnichannel strategy, including data silos, technology integration, and maintaining consistency across numerous channels. It provides insights into overcoming these challenges through strategic planning, technological investment, and cross-departmental collaboration. Additionally, the paper highlights critical metrics and attribution models that businesses can use to measure the success of their omnichannel efforts, offering a comprehensive view of how different touchpoints contribute to customer engagement, loyalty, and lifetime value. Through a robust analysis, this paper provides actionable recommendations for businesses seeking to harness the power of omnichannel marketing to foster stronger customer relationships, enhance brand loyalty, and achieve sustainable growth in an increasingly competitive marketplace.